Substance Use Among Adolescents and Young Adults With Type 1 Diabetes: Discussions in Routine Diabetes Care. (May 2020) - Bento, Samantha P.; Campbell, MaryJane S.; Soutullo, Olivia; Cogen, Fran R.; Monaghan, Maureen
Pediatric health care providers are in a unique position to discuss the health implications of alcohol, tobacco, and drug use with adolescents and young adults (AYAs) with type 1 diabetes (T1D). This study evaluated the frequency of self-reported substance use and associated demographic and clinical characteristics in a sample of AYAs with T1D and patient-provider discussions of substance use in T1D care. Sixty-four AYAs completed questions about substance use from the Youth Risk Behavior Survey (YRBS). Corresponding diabetes clinic visits were audio-recorded, transcribed, and reviewed to examine substance use discussions. A total of 56.3% of AYAs reported ever engaging in substance use; 40.6% reported substance use within the past 30 days. Five AYAs had discussions about substance use during their most recent diabetes clinic visit. Substance use should be proactively addressed by pediatric health care providers and AYAs should be encouraged to raise questions related to substance use during clinic visits.